THE USE OF SOCIAL MEDIA IN RICE CULTIVATION TECHNIQUES IN BAUMATA VILLAGE, TAEBENU DISTRICT, KUPANG REGENCY - Embot, Karolina Yunita; Olviana, Tomycho; Chamdra, Santhy (Buletin Ilmiah Impas, 2025)
This study aims to explore the use of social media in agricultural extension to improve farmers' knowledge of rice cultivation techniques, as well as to identify the obstacles faced. The research method used is descriptive qualitative and quantitative, with data collected through interviews, observation, and documentation involving 38 farmers selected using purposive sampling. The results show that the most commonly used social media platforms are WhatsApp and Facebook (100%), followed by YouTube (78.9%). WhatsApp is considered the most effective because it supports direct communication between farmers and extension workers. Facebook is used but deemed less practical due to its entertainment-focused content. YouTube is helpful for extension videos but limited by internet data constraints. The main obstacles in using social media are the limited financial ability to purchase internet data and weak internet access in some areas.